Higher education and global flow of information and idea among youths: explanation for youth and ICT as agents for change (2010)
This paper examined higher education and the global flow of information and ideas among youths and explanation for youth and ICT as agents for changes in our society, in terms of assessing information, and the utilisation of information via-internet and education to better their lots in terms of connection and employment outside their country of residence. This paper also looks at how a global forum for youths in ICT education could be organised, and the benefits attributed to this forum were discussed. The paper therefore recommends that education in ICT should be made compulsory for the youths, and the internet should also be made accessible freely for youths in schools.